Rapamycin transiently induces mitochondrial remodeling to reprogram energy metabolism in old hearts - Chiao, Ying Ann (Aging (Albany NY), 2016)
Rapamycin, an inhibitor of mTOR signaling, has been shown to reverse diastolic dysfunction in old mice in 10 weeks, highlighting its therapeutic potential for a poorly treatable condition. However, the mechanisms and temporal regulation of its cardiac benefits remain unclear. We show that improved diastolic function in old mice begins at 2-4 weeks, progressing over the course of 10-week treatment. While TORC1-mediated S6 phosphorylation and TORC2 mediated AKT and PKCα phosphorylation are inhibited throughout the course of treatment, rapamycin inhibits ULK phosphorylation and induces autophagy during just the first week of treatment, returning to baseline at two weeks and after. Concordantly, markers of mitochondrial biogenesis increase over the first two weeks of treatment and return to control levels thereafter. This transient induction of autophagy and mitochondrial biogenesis suggests that damaged mitochondria are replaced by newly synthesized ones to rejuvenate mitochondrial homeostasis. This remodeling is shown to rapidly reverse the age-related reduction in fatty acid oxidation to restore a more youthful substrate utilization and energetic profile in old isolated perfused hearts, and modulates the myocardial metabolome in vivo. This study demonstrates the differential and dynamic mechanisms following rapamycin treatment and highlights the importance of understanding the temporal regulation of rapamycin effects.